FORMAL MALE GARMENT FROM THE LATE 15th CENTURY: Necropolis at Vodoča, Grave 934 (Annual of the Faculty of Philosophy in Skopje, 2010)
Grave 934 on the site of the Vodoča Church Complex, Church of St. Leontius in the village of Vodoča near Strumica belonged to a young, robust man. Fig. 1. He wore a bronze seal ring on his right hand, with a deeply carved ornament in the shape of a “fir tree branch” (?) dated to the late 15th century. (Fig. 2-3)On his chest, two hollow, ball-shaped small buttons have been discovered which were used for the buttoning of a lighter piece of garment (Fig. 4(1.2)), as well as four large lavishly crafted buttons in the shape of a semi-calotte sowed onto the more bulky upper part of the garment. Fig. 5 i.4.Their appearance is unique, as well as the decoration on the visible upper round surface (a combination of small rosettes, imitation of filigree and granulation). Their shape indicates that they should be dated to the 15th century.The arrangement on the large buttons on the garment from Grave 934 has its analogies in the depiction of male pieces of clothing in the donors’ compositions in the fresco painting from the wider region dating from the period between the late 14th century and the last decades of the 15th century.
Keywords: NECROPOLIS; VODOCHA; RING; BUTTONS; DONORS’ COMPOSITIONS; FRESCO PAINTING